Акустичні радіоелектронні системи - Сібіркін, А. С. (ХНУРЕ, 2025)
The advancement of acoustic radio-electronic systems plays a crucial role in modern technologies, particularly in sonar applications, non-destructive testing, and environmental monitoring. These systems integrate acoustic wave propagation principles with electronic signal processing to detect and analyze objects in various media. Sonar-based navigation in submarines, ultrasound imaging in medicine, and structural health monitoring in civil engineering are among the key applications. This study examines the latest developments in acoustic radio-electronic systems, highlighting their role in security, industrial diagnostics, and scientific research.
Keywords: акустична радіоелектронна система; acoustic radio-electronic system